Governance and Community Perceptions in Ly Son Island and Sa Huynh Beach Area, Quang Ngai Province, Vietnam - Phan Vinh, Vinh (JMET: Journal of Management Entrepreneurship and Tourism, 2025)
Sustainable tourism development necessitates adaptive governance frameworks that prioritize both the perceptions and active engagement of local communities. This study investigates the perspectives of long-term residents in two emerging coastal destinations in Quang Ngai province–Ly Son Island and the Sa Huynh Beach Area–with regard to the perceived impacts of tourism. Data were collected from a randomly selected sample of 300 residents using a structured questionnaire based on a five-point Likert scale. The Kruskal-Wallis H test indicated statistically significant differences between the two sites. Respondents in Ly Son Island showed a more explicit awareness of both the positive outcomes of tourism (e.g., job creation, infrastructure development) and its adverse effects (e.g., environmental degradation, overcrowding). Conversely, residents in the Sa Huynh Beach Area expressed more cautious views, likely reflecting the nascent stage of tourism development in the locality. Drawing on these findings, the study recommends destination-specific governance strategies: for Ly Son Island, a more regulated development model with enhanced mechanisms for community consultation is suggested; for the Sa Huynh Beach Area, efforts should center on capacity building and the promotion of community-based tourism initiatives.